Pottery, people, and politics: a case from southern Arabia - Glanzman, W.D. (Proceedings of the Seminar for Arabian Studies, 2014)
A re-examination of Peter J. Parr's 1978 thesis concerning the distribution of Nabataean painted wares within and beyond the territory of Nabataean political and economic influence, focuses on finds from southern Arabia: the western portion of Dhōfar within the Sultanate of Oman; the Mārib Governate in the Republic of Yemen; and the ʿAsīr, the south-western region of the Kingdom of Saudi Arabia. While commerce is usually invoked for the presence of such wares, the rarity with which they are found outside the Nabataean political domain suggests another view is needed; ceramics reflect the presence of Nabataean elites both at caravan stations and maritime ports. These wares can be placed within a specific time frame, prior to AD 106.